Number of women on boards of large firms increasing slowly: Legal requirements could provide momentum - Anja Kirsch; Katharina Wrohlich (DIW Weekly Report, 2021)
The proportion of women on the boards of large companies in Germany continued to increase during 2020. In the fourth quarter of 2020, there were 101 female executive board members in the 200 largest companies, seven more than in 2019. However, growth was slow, as it was in some of the other groups of companies as well: The proportion of women on the executive boards of the top 200 companies (around 12 percent) was only one percentage point higher than in 2019. For the first time since 2013, there was even a stagnation in the proportion of women on the executive boards of the DAX 30 companies. The minimum requirement for the participation of women on executive boards, a bill adopted by the German Federal Cabinet at the beginning of 2021, could provide a push in growth. In its current form, it applies to 74 companies, around 30 of which are not yet in adherence. If all 74 companies become compliant, the proportion of female executive directors in these companies would increase from around 13 to 21 percent. In addition, the planned legislation could generate momentum for greater gender equality far beyond the boardroom. The developments on supervisory boards underscore the fact that legally binding requirements are effective.
Keywords: D22; J16; J59; J78; L21; L32; M14; M51; 330; corporate boards; board composition; boards of directors; boarddiversity; Europe; women directors; gender equality; gender quota; Germany; management; private companies; public companies; supervisory boards; executiveboards; CEOs; women; finance industry; financial sector; private and public banks; insurance companies